Intensive fishery scenarios on the North Patagonian coast (Río Negro, Argentina) during the Mid-Holocene - Favier Dubois, Cristian Mario (2012)
In contrast to what was recorded in other sectors of the Atlantic coast of continental Patagonia, evidence of intensive fishing activities has been found on the northern littoral of the San Matías Gulf (Río Negro, Argentina). The archaeological evidence of this practice, that go back to around 6000 14C BP, consists mainly of fish remains (white croaker otoliths) preserved on the surface of Pleistocene marine terraces together with weights for nets and other lithic artifacts involved in the primary processing of this resource. It is proposed that under the prevailing arid conditions in Mid-Holocene times in northeastern Patagonia, the productivity and particular configuration of the coast during the marine transgression at the studied localities would have offered a very favorable framework for the early development of this practice in the area.